ANALISIS KESALAHAN PESERTA DIDIK DALAM MENYELESAIKAN SOAL CERITA BERDASARKAN PROSEDUR NEWMAN - Nur Qoiriyah; Djoko Adi Susilo; Sri Hariyani (SIGMA, 2021)
The purpose of this study is to explore information about the challenges, difficulties, and mistakes that experienced by students in solving passage questions with the material of the Linear System with Two-Variable based on the Newman procedure. This research is qualitative research with a descriptive approach. The subjects of the research consisted of 6 students from 31 students eight grade of MTs. Miftahul Ulum Bululawang with 2 upper groups, 2 intermediate groups, and 2 lower groups. The data are collected using exercises (question and answer) and interviews. The data validity test was performed by using triangulation techniques. Data analysis is carried out based on Newman's error indicators, those are reading, understanding the problem (Comprehension), transforming the problem (Transformation), process skills, and writing the final answer (Encoding). The results of this study indicate that the mistakes made by the upper group are the type of misreading (Reading), understanding the problem (Comprehension), transformation problem (Transformation), processing skills problem (Process Skills), and problem in writing the final answer (Encoding). The types of mistakes that the intermediate group made are reading, process skills, and final answer writing (Encoding). The type of mistakes made by the lower group is reading (Reading). Students do not write the variables used for example.